Sustainable biofouling mitigation: Advancing maritime efficiency and environmental protection - Yok Suprobo; R. Riyanto; Susi Herawati (University of Muhammadiyah Malang, 2025)
Biofouling on ship hulls significantly impacts maritime operations by increasing drag, fuel consumption, and greenhouse gas emissions, while traditional antifouling methods often harm marine ecosystems. This research explores innovative biofouling mitigation strategies, focusing on bio-based coatings and active antifouling systems to enhance operational efficiency and sustainability. By integrating qualitative insights from 13 maritime professionals, 24 educators, and 33 graduates, the study evaluates the effectiveness, environmental benefits, and practical applications of these strategies. The findings reveal that bio-based coatings and active systems outperform traditional methods in fuel efficiency, drag reduction, and environmental sustainability, offering economically and ecologically viable alternatives. The study also highlights the importance of interdisciplinary collaboration and knowledge-sharing in developing and implementing these solutions. Practical implications include cost savings, reduced emissions, and the integration of advanced antifouling technologies into maritime vocational education, ensuring a skilled workforce equipped to address future challenges. These results contribute to the advancement of sustainable practices in the maritime industry, aligning with global decarbonization and environmental protection goals.